Hubungan Pengetahuan Remaja tentang Kesehatan Reproduksi dengan Perilaku Seksual Beresiko di SMA Esa Prakarsa Selesai Kabupaten Langkat - Elvi Era Liesmayani; Dewi Susanti; Syahbaniah Ginting (Jurnal Bidan Mandiri, 2023)
Adolescence is the most prone period in physical life, growth, and development since sexual hormone has actively functioned. Naturally, teenagers experience rapid sexual drive which can cause the existence of risky sexual behavior. The objective of the research was to find out the correlation between teenagers’ knowledge of reproduction health and their sexual behavior at SMA Esa Prakarsa, Selesai, Langkat District, in 2014. The research was an analytic survey with cross sectional design. The population was 156 Grade XI students at SMA Esa Prakarsa, Selesai, Langkat District, and 114 of them were used as the samples. The data were analyzed by using univatriate analysis and bivatriate analysis with chi square test. The result of the research showed that 45 respondents (34,5%) lack of knowledge of high risky sexual behavior, and 11 respondents (9,6%) had low risky sexual behavior with p-value = 0.000 which indicated that p-value = 0,000 < 0,05. The conclusion of the research was that, statistically, there was significant correlation between teenagers’ knowledge of reproduction health and risky sexual behavior at SMA Esa Prakarsa, Selesai, Langkat District, in 2014.